2004
DOI: 10.1038/sj.jhh.1001779
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and atherosclerotic plaques in carotid, aortic and femoral arteries in elderly Finns with diabetes mellitus or impaired glucose tolerance

Abstract: The aim of the study was to evaluate the occurrence of atheromatous plaques in carotid, aortic and femoral arteries, focusing on blood pressure (BP). The study subjects consisted of 65-year-old Finns drawn from a population-based cohort. Ultrasonographic measurements were performed on 54 diabetic subjects, 97 subjects with impaired glucose tolerance (IGT) and 57 normoglycaemic subjects (NGT). High systolic BP (SBP) was defined as X160 mmHg and high diastolic BP as X95 mmHg. High pulse pressure (PP) was defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
(57 reference statements)
2
13
0
1
Order By: Relevance
“…The average levels of total, HDL, and LDL cholesterol, diastolic blood pressure, and GFR were consistent with the general elderly population in this age range. Systolic blood pressure was higher than in the general population but similar to that observed in other T2D samples [22]. Most subjects were treated with oral anti-diabetic medications (79%), 1% were treated with insulin only, 9% were treated with a combined therapy of oral anti-diabetic medications and insulin and 11% were controlled by diet only.…”
Section: Resultssupporting
confidence: 80%
“…The average levels of total, HDL, and LDL cholesterol, diastolic blood pressure, and GFR were consistent with the general elderly population in this age range. Systolic blood pressure was higher than in the general population but similar to that observed in other T2D samples [22]. Most subjects were treated with oral anti-diabetic medications (79%), 1% were treated with insulin only, 9% were treated with a combined therapy of oral anti-diabetic medications and insulin and 11% were controlled by diet only.…”
Section: Resultssupporting
confidence: 80%
“…However, presence of atherosclerosis at this aforementioned site may also be a marker of the disease in the more peripheral arterial branches. In support, studies demonstrated that presence of atherosclerotic plaques is frequently associated with plaques at other anatomical sites such as the carotid and femoral arteries [13, 14].…”
Section: Discussionmentioning
confidence: 98%
“…Arterial plaque was defined as an echogenic structure encroaching into the vessel lumen with a distinct area and resulting in >50% greater IMT compared with the neighbouring sites (Giral et al 1991). A more detailed description of the ultrasound examinations is presented in studies by Rajala et al (2005a, b). In this paper, we used the total number of aortic, carotid and femoral plaques, the total number of plaques in the carotid arteries on both sides, the number of aorta plaques and the mean of IMT as outcome variables.…”
Section: Methodsmentioning
confidence: 99%